Evolving trends and driving factors analysis of green development level in Chengdu plain economic zone - Ma, Li; Huang, Tianzhi; Chen, Hao; Mao, Jiankang; Cheng, Zhongqi; Wang, Yingwei (Frontiers in Environmental Science, 2025)
Green development is key to promoting high-quality regional development. Chengdu Plain Economic Zone (CPEZ) stands as the primary area for the Chengdu-Chongqing twin-city economic circle. This study constructed an evaluation system for green development level, selecting 33 indicators from three dimensions: green environment, green lifestyle, and green economy. Through the application of the entropy-TOPSIS method, Pearson correlation analysis, and geographic detector, the green development level of the Chengdu Plain Economic Zone urban agglomeration from 2013 to 2022 was evaluated, as well as the coupling and coordination relationship of green development was analyzed, and the driving mechanism affecting the green development of the region was explored. The results show that: (1) The overall level of green development in the research area continues to improve from 2013 to 2022, with an average annual growth rate of 5.11%. There is spatial heterogeneity in the level of green development among cities. (2). The coupling coordinated development degree (CCD) has steadily improved, however, the overall region is still in a low-level stage of coupled coordinated development. Among them, Ziyang, Suining, Mianyang, and Ya’an exceeded the regional average level in 2015, 2017, 2018, and 2019 respectively, entering the stage of primary coupling and coordinated development. (3). The key driving factors for green development level include GDP electricity consumption, per capita length of water supply pipelines, percentage of added value of the secondary and tertiary industries to GDP, per capita water resources, and population density. The spatial differences in these indicators explain over 50% of the level of green development. To promote high-quality development of the CPEZ, three policy recommendations are proposed: Firstly, optimize green environmental governance. The second is to encourage the development of green technology innovation and circular economy. The third is to strengthen the coordinated development of regional economy, optimize the allocation of resource elements, enhance the radiation effect of urban agglomerations, and drive the integrated development of the CPEZ.